Contrasting effects of landscape features on genetic structure in different geographic regions in the ornate dragon lizard, Ctenophorus ornatus. Issue 15 (25th July 2013) - Levy, Esther; Tomkins, Joseph L.; LeBas, Natasha R.; Kennington, W. Jason
Abstract: Habitat fragmentation can have profound effects on the distribution of genetic variation within and between populations. Previously, we showed that in the ornate dragon lizard, Ctenophorus ornatus, lizards residing on outcrops that are separated by cleared agricultural land are significantly more isolated and hold less genetic variation than lizards residing on neighbouring outcrops connected by undisturbed native vegetation. Here, we extend the fine‐scale study to examine the pattern of genetic variation and population structure across the species' range. Using a landscape genetics approach, we test whether land clearing for agricultural purposes has affected the population structure of the ornate dragon lizard. We found significant genetic differentiation between outcrop populations ( F ST  = 0.12), as well as isolation by distance within each geographic region. In support of our previous study, land clearing was associated with higher genetic divergences between outcrops and lower genetic variation within outcrops, but only in the region that had been exposed to intense agriculture for the longest period of time. No other landscape features influenced population structure in any geographic region. These results show that the effects of landscape features can vary across species' ranges and suggest there may be a temporal lag in response to contemporary changes in land use. These findings therefore highlight the need for caution when assessing the impact of contemporary land use practices on genetic variation and population structure.